Matrix-assisted laser desorption-ionization time-of-flight mass spectrometry for the identification of Neisseria gonorrhoeae. (September 2016) - Buchanan, R.; Ball, D.; Dolphin, H.; Dave, J.
Abstract: Matrix-assisted laser desorption-ionization time-of-flight mass spectrometry (MALDI-TOF MS) was compared with the API NH biochemical method for the identification of Neisseria gonorrhoeae in routine clinical samples. A retrospective review of laboratory records for 1090 isolates for which both biochemical and MALDI-TOF MS identifications were available was performed. Cases of discrepant results were examined in detail for evidence supportive of a particular organism identification. Of 1090 isolates, 1082 were identified as N. gonorrhoeae by API NH. MALDI-TOF MS successfully identified 984 (91%) of these after one analysis, rising to 1081 (99.9%) after two analyses, with a positive predictive value of 99.3%. For those isolates requiring a repeat analysis, failure to generate an identifiable proteomic signature was the reason in 76% of cases, with alternative initial identifications accounting for the remaining 24%. MALDI-TOF MS identified eight isolates as N. gonorrhoeae that were not identified as such by API NH—examination of these discrepant results suggested that the MALDI-TOF MS identification may be the more reliable. MALDI-TOF MS is at least as accurate and reliable a method of identifying N. gonorrhoeae as API NH. We propose that MALDI-TOF MS could potentially be used as a single method for N. gonorrhoeae identification in routine cases by laboratories with access to this technology.